Needs-analysis to the Sasaknese Locality-Embedded English Curriculum Development for Tourim Vocational High Schools - Dedi Aprianto (Universitas Islam Negeri (UIN) Mataram, 2021)
This study as a part of the process of English curriculum development aimed to examine the existing problems of the current curriculum implementation and the target needs and learning needs (local wisdom insertion). It drew on focus group discussion, interview, and content analysis. The results of the target need analysis on local knowledge and language competence for developing skills and abilities, needs-based, and contextual learning showed that a lack of the gaps as the fundamental problems elicited from the current curriculum. It was also found that in terms of Wants, the students preferred to knowledge and vocational background-based curriculum contents. English learning design was associated with tourism competencies embedded with local wisdom. The local wisdom can be developed into the English curriculum; values of knowledge, social norms, and cultural acculturations, the marriage systems, patterns of family, and the other social-cultural activities, and the elements of aesthetics. The study encapsulates that English teachers need to initiate developing a local wealth-based English curriculum in favor of orienting the students to develop local knowledge.